Testicular steroid sulfatase overexpression is associated with Leydig cell dysfunction in primary spermatogenic failure. (30th December 2020) - Lardone, Maria C.; Reyes, Ian N.; Ortiz, Eliana; Piottante, Antonio; Palma, Cristián; Ebensperger, Mauricio; Castro, Andrea
Abstract: Background: Decreased testosterone (T) to LH ratio and increased 17β‐estradiol (E2) serum concentrations represent a common finding among patients with severe spermatogenic failure, suggesting a concurrent Leydig cell steroidogenic dysfunction. Aromatase overexpression has been associated with increased serum and intratesticular E2 in these patients. However, it is unknown whether the sulfatase pathway contributes to the increased availability of active estrogens in patients with primary spermatogenic failure. Objectives: To assess estrogen sulfotransferase (SULT1E1) and steroid sulfatase (STS) mRNA abundance in testicular tissue of patients with Sertoli cell‐only syndrome (SCOS) and normal tissues, its association with serum and intratesticular hormone levels, and to explore the mRNA and protein testicular localization of both enzymes. Materials and Methods: Testicular tissues of 23 subjects with SCOS (cases) and 22 patients with obstructive azoospermia and normal spermatogenesis (controls) were obtained after biopsy. SULT1E1 and STS transcripts accumulation was quantified by RT‐qPCR. For mRNA and protein localization, we performed RT‐qPCR in Leydig cell clusters and seminiferous tubules isolated by laser‐capture microdissection and immunofluorescence in testicular tissues. Serum and intratesticular hormones were measured by immunoradiometric assays. Results: SULT1E1 mRNA accumulation was similar in both groups. The amount of STS mRNA was higher in cases ( p  = 0.007) and inversely correlated with T/LH ratio ( r  = −0.402; p  = 0.02). Also, a near significant correlation was observed with intratesticular E2 ( r  = 0.329, p  = 0.057), in agreement with higher intratesticular E2 in cases ( p  < 0.001). Strong STS immunoreaction was localized in the wall of small blood vessels but not in Leydig cells. Both SULT1E1 and STS mRNA abundance was similar in Leydig cell clusters and the tubular compartment, except for lower SUTL1E1 mRNA in the seminiferous tubules of SCOS patients ( p  = 0.001). Conclusions: Our results suggest that an unbalance of the STS/SULT1E1 pathway contributes to the testicular hyperestrogenic microenvironment in patients with primary spermatogenic failure and Leydig cell dysfunction.